Chapter 4 Styles of Theorizing International Practice - Bueger, Christian (Bristol University Press, 2022)
The digital pdf of Chapter 4 is available Open Access under CC-BY-NC-ND licence. This collection brings together leading figures in the study of international relations to explore praxis as a perspective on international politics and law. With its focus on competent judgments, the praxis approach holds the promise to overcome the divide between knowing and acting that marks positivist international relations theory. Building on the transdisciplinary work of Friedrich Kratochwil, this book reveals the scope, limits and blind spots of praxis theorizing.